The Distribution of Analcite in the Newcastle Coal Measure Sediments of the Sydney Basin (The Australasian Institute of Mining and Metallurgy, 1967)
An attempt was made to determine the lateral extent of analcite in the Newcastle Coal Measure sediments of the Sydney Basin. From an examination of the cores of eleven bores it was concluded that the mineral is concentrated in the western sector of the original Newcastle Basin and this presumably was the region of greatest sodium concentration and aridity. The distribution of the analcite is such that it appears to have little correlative value.